490 = 2 ⋅ 5 ⋅ 72
900 = 2 2 ⋅ 32 ⋅ 52
gcd(490, 900) = 2 ⋅ 5
lcm(490, 900) = 22 ⋅ 32 ⋅ 52 ⋅ 72 ⋅
A = {1, 2, 3, 5, 8, 13}Fill in the table below indicating the set that the expression evaluates to.
B = {1, 2, 3, 4, 5, 6, 7}
C = {5, 7, 9, 11, 13, 15}
Expression | Value |
---|---|
(A ∩ B) ∪ (A ∩ C) | {1, 2, 3, 5, 13} |
C ∩ (A ∪ B) | {5, 7, 13} |
C ∩ B | {9, 11, 13, 15} |
B ∪ C | {8, 10, 12, 14} |
A = {x | x ∈ R ∧ x ≥ 1}Fill in the table below indicating "yes" or "no" whether the given function is onto and one-to-one for the given mapping.
B = {x | x ∈ R ∧ 0 ≤ x ≤ 1}
C = {x | x ∈ R ∧ -1 ≤ x ≤ 1}
Function | Mapping | Onto? | One-to-One? |
---|---|---|---|
f(x) = 1/x | A → B | no | yes |
f(x) = x2 | B → C | no | yes |
f(x) = x2 | B → B | yes | yes |
f(x) = x2 | C → B | yes | no |
Rude(x) means that x is a rude person
Selfish(x) means that x is a selfish person
Criticize(x, y) means that x criticizes y
For the first three problems below, translate the given sentence into predicate logic using quantifiers when appropriate. No negation should appear in front of a quantifier or in front of a parenthesized expression.
(5 points) Everyone criticizes each of the selfish people.
∀x (Selfish(x) → ∀y Criticize(y, x))
(5 points) Some rude people are criticized by all of the selfish people.
∃x (Rude(x) ∧ ∀y (Selfish(y) → Criticize(y, x)))
(5 points) Only people who are either rude or selfish are criticized by other people.
∀x (∃y Criticize(y, x) → (Rude(x) ∨ Selfish(x)))
∀x ∀y(Criticize(y, x) → (Rude(x) ∨ Selfish(x)))
(5 points) Translate the following predicate into English:
∃x (Criticize(x, x) ∧ ∀y (Criticize(y, y) → x = y))There is exactly one person who criticizes himself.
(4 points) John is 21 or older.
yes by 3, 1
(4 points) Phillip cannot legally buy alcohol.
yes by 7, 4
(4 points) Susan can legally buy alcohol.
no (cannot be concluded)
(4 points) Martha is not 21 or older.
no (cannot be concluded)
(4 points) John can vote.
yes by 3, 1, 6
We can use a direct proof. Assume that the difference between n and m is even. Then we know that:
n - m = 2k for some integer kWe now show that n2 - m2 is even:
n2 - m2 = (n - m)(n + m) = 2k(n + m)Because n2 - m2 can be expressed as 2 times an integer, it must be even. This completes the proof.
We can prove this using a proof by contradiction. Assume that the proposition is false. Then there is some integer n for which 4 does not divide n2 - 1 and n is odd. By the definition of odd numbers, we know that:n = 2k + 1 for some integer kBut then we have:
n2 - 1 = (2k + 1)2 - 1
= 4k2 + 4k + 1 - 1
= 4k2 + 4k
= 4(k2 + k)In other words, 4 divides n2 - 1, which contradicts our original assumption. Thus, we have proven that for all integers n, either 4 divides n2 - 1 or n is even.
2/5 + 2/52 + 2/53 ... + 2/5n = 1/2 - 1/(2 ⋅ 5n)Provide a formal definition for the overall proposition being proved (P(n)) using summation notation and indicate the domain for n. Then provide an inductive proof, clearly indicating where you are applying the inductive hypothesis.
Let P(n) be the statement that:We can prove that P(n) holds for n ∈ Z+ using induction.
n
∑
i = 12/5i = 1/2 - 1/(2 ⋅ 5n) We first prove P(1):
2/5 = 3/10 = (5 - 2)/10 = 5/10 - 2/10 = 1/2 - 1/(2 ⋅ 51)Then we assume P(k) for some k ∈ Z+:And we prove P(k + 1):
k
∑
i = 12/5i = 1/2 - 1/(2 ⋅ 5k)
k + 1
∑
i = 12/5i = 1/2 - 1/(2 ⋅ 5k + 1)
k + 1
∑
i = 12/5i = (by inductive hypothesis)
k
∑
i = 12/5i + 2/5k + 1=
= 1/2 - 1/(2 ⋅ 5k) + 2/5k + 1
= 1/2 - 5/(2 ⋅ 5k + 1) + 4/(2 ⋅ 5k + 1)
= 1/2 - (5 - 4)/(2 ⋅ 5k + 1)
= 1/2 - 1/(2 ⋅ 5k + 1)
Therefore P(n) holds for all n ∈ Z+.